The Rieske Iron-Sulfur Protein: Import and Assembly into the Cytochrome 𝑏𝑐1 Complex of Yeast Mitochondria - Laura Conte; Vincenzo Zara (Bioinorganic Chemistry and Applications)
The Rieske iron-sulfur protein, one of the catalytic subunits of the cytochrome 𝑏𝑐1 complex, is involved in electron transfer at the level of the inner membrane of yeast mitochondria. The Rieske iron-sulfur protein is encoded by nuclear DNA and, after being synthesized in the cytosol, is imported into mitochondria with the help of a cleavable N-terminal presequence. The imported protein, besides incorporating the 2Fe-2S cluster, also interacts with other catalytic and non-catalytic subunits of the cytochrome 𝑏𝑐1 complex, thereby assembling into the mature and functional respiratory complex. In this paper, we summarize the most recent findings on the import and assembly of the Rieske iron-sulfur protein into Saccharomyces cerevisiae mitochondria, also discussing a possible role of this protein both in the dimerization of the cytochrome 𝑏𝑐1 complex and in the interaction of this homodimer with other complexes of the mitochondrial respiratory chain.